Cognitive Approaches to Disaster Communication: Mass Media’s Role in Tsunami Preparedness - Harnita, Pratiwi Cristin; Krisnawati, Ester; Nur Imanah, Norif Didik; Rusana, Rusana; Abraham, Rendy Hermanto (Jurnal The Messenger, 2023)
Introduction: This study explored the role of mass media in enhancing tsunami preparedness among young adults on the southern coast of Central Java, a region highly vulnerability to tectonic events. Mass media, with its extensive reach and persuasive influence, played a significant role in disaster communication, shaping public awareness and preparedness. Methods: Guided by Elaboration Likelihood Model (ELM) and neuroscience perspectives, the research examined how cognitive and emotional responses to disaster information influenced preparedness behaviors. A survey was conducted with 175 respondents aged 18-24 from Calaca, a high-risk tsunami zone. Among these, 91 respondents had prior disaster experience, with 60.38% relying on mass media as their primary source of emergency information. Findings: The survey results showed that 74.9% of respondents indicated readiness for disaster preparedness. The study integrated the ELM framework with cognitive neuroscience, emphasizing modification to critical element such as ability to process information and the nature of cognitive processing. These adaptations supported more effective, persuasive disaster communication. Originality: The finding underscored the potential of mass media as powerful stimulus, shaping cognitive responses and preparedness behavior. This research contributed to understanding the interplay between disaster communication, cognitive processes, and behavioral outcomes, offering insights for designing targeted interventions to enhance preparedness.